Pengaruh Informasi Laba Akuntansi dan Informasi Corporate Social Responsibility Pada Return Saham : (Studi Perusahaan Sub Sektor Perbankan pada Bursa Efek Indonesia) - Sufyan Saori; Umaimah Umaimah (BADAN PENERBIT STIEPARI PRESS, 2024)
This research is motivated by the strategic function of the banking industry in handling the impact of the pandemic and the increasing interest in investment in the banking sub-sector by investors. Therefore, the stock price of the banking sub-sector after the pandemic tends to increase in tandem with the improvement in the national economy. This study will further examine the effect of accounting earnings information and corporate social responsibility information on stock returns. This information is now the basis for investment decisions because it contains related and non-financial information that is important to the operations of the sample companies taken based on predetermined criteria, namely banking sub-sector companies listed on the IDX and publishing financial reports and annual reports throughout 2019 to 2021. After determined, the sample was selected using purposive sampling according to the criteria and obtained a total of 35 companies. The data is then processed using a quantitative approach with multiple linear regression method because it uses two independent variables. After processing, the results obtained are accounting profit information and corporate social responsibility information have a negative effect on stock returns.